Physicochemical Parameters Optimization and Peroxidase Characterization from Aspergillus niger Native Strain by Solid-State Fermentation for Improved Dye Decolorization - Shiv Ram Ashraf; Amber Afroz; Zahid Anwar (BioResources, 2023)
The hyper yield of peroxidase (POX) was investigated for a novel native Aspergillus niger strain identified by 18S RNA analysis. A. niger strains sequences were submitted to GenBank; IDs allotted were MN611114.1 (BMB 17) and MN559756.1 (BMB-18). The identified Aspergillus strains in combination showed enhanced (POX) activity (601.5 U/mL) by solid-state fermentation in comparison to their individual activities. POX was purified by ammonium sulfate, and size exclusion gel chromatography exhibited a 7.83-fold increase in POX concentration (13.3 U/mg) in comparison to BMB17 and BMB 18 (11.8 & 7.6 U/mg respectively). The best POX activity was obtained with pH 6.5, 37 °C, and 5 days of incubation. Using guaiacol as substrate, POX showed maximum activity (Vmax) of 537 U/mL with a corresponding Michaelis constant (Km) value of 126 µM. Calcium chloride worked as a POX activator at 300 & 400 mM. Zinc sulfate (500 mM), EDTA (5 mM); ethanol, propanol, and acetonitrile (50%) inhibited (18-30%) POX. Urea (1M), and copper sulfate (500 mM) strongly inhibited POX up to 40%. Polysorbate-80 (1%) slightly reduced the POX by 10% to 15%. BMB17+18-induced promising dye decolorization (88-98%) against all vat dyes, methylene blue, and phenol red.